Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1080/00016470410001439
|View full text |Cite
|
Sign up to set email alerts
|

Do we really need to routinely crossmatch blood before primary total knee or hip arthroplasty?

Abstract: For routine primary THR/TKR, GS policy is a safe procedure. Reduction in non-utilisation of blood has economic and cost-saving implications for limited healthcare resources. Having subsequently introduced a group-and-save policy for all patients undergoing routine THR/TKR, considerable savings have been identified after only 2 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 2 publications
0
7
0
2
Order By: Relevance
“…15 In addition, we routinely stop the administration of NSAIDS five days before surgery since they may increase peri-operative blood loss and transfusion requirements. 16 We have reported a transfusion rate of less than 20% for all patients who have undergone lower-limb arthroplasty in our hospital. 17 The remaining asymptomatic patients had previously been treated with ferrous sulphate (200 mg three times daily) which is a recognised oral treatment for iron-deficiency anaemia.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…15 In addition, we routinely stop the administration of NSAIDS five days before surgery since they may increase peri-operative blood loss and transfusion requirements. 16 We have reported a transfusion rate of less than 20% for all patients who have undergone lower-limb arthroplasty in our hospital. 17 The remaining asymptomatic patients had previously been treated with ferrous sulphate (200 mg three times daily) which is a recognised oral treatment for iron-deficiency anaemia.…”
Section: Discussionmentioning
confidence: 76%
“…Between June 11 and March 31, 2003, 334 patients were screened for inclusion in the study of whom 207 were ineligible for the following reasons: low haemoglobin (46), low platelet count (6), raised CRP (28), a past history of cancer (16), abnormal renal function (15), low serum ferritin (16), current administration of iron supplements (21), and unwillingness to participate (84). Some were ineligible Table I.…”
Section: Resultsmentioning
confidence: 99%
“…The proportion of female patients in TKA studies, however, is usually high and it varies between 70 to 90 percent, as in our analyzed studies. Transfusion use in TKA is also widely variable depending on the centers, and it has been reported a transfusion rate between 4 to 72 percent 22‐24 . Six (67%) of nine RCTs reported a treatment effect favoring the use of TA for reducing blood transfusion in patients undergoing TKA, whereas the remainding three (33%) studies showed no advantage to the administration of TA.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to increased waste, larger inventories, and increased departmental costs. 4,9,12,13 Other variables must be considered to effectively assess the need for crossmatching units to a patient and include: preoperative hemoglobin level, predicted blood loss, patient blood volume and likelihood of transfusion 5,6,9,12,13 These variables should all be used in conjunction to evaluate patient needs.…”
Section: Discussionmentioning
confidence: 99%
“…This is a widely accepted method to monitor product use, a 2.0 benchmark is generally considered appropriate. 8,13,14 Apparent in a United Kingdom study, Mundy et al 9 concluded that 77% of total hip and 62% of total knee surgeries requested units which were never used.…”
Section: Introductionmentioning
confidence: 99%